ANALISIS PERANCANGAN MEDIA PEMBELAJARAN ANIMASI INTERAKTIF MENGENAL BAHASA JEPANG - Komarudin, Rachman; Noor, Ridha Rifiana (Jurnal Pilar Nusa Mandiri, 2017)
Analysis of animation instructional media interkatif know Japanese language aims to obtain a feasibility study media based on test validity and reliability and also to study the response of the user (user) regarding this interactive learning media. whereas in the design of interactive media is using the meotde development of multimedia applications, the steps being taken is the concept, design, material collecting, assembly, testing, and distribution (implementation). The results of calculations with the validity and reliability is obtained that the significance level (α) = 5% = 0.05. by using statistical test r-Spearman (Spearman rho) obtained critical value = value table (n-28) rtabel = rα; (N-2) = r 0:05; (28) = 0.3610. If tested the validity of each variable can be considered valid indicator entirely because r count larger than r table, and to test the reliability value of Cronbach's Alpha 0734 is greater than rtabel 0.3610. so its value is valid. It can be concluded that the media interactive animated learning Japanese language decent used to know.